Familial clustering of congenital deafness, patent ductus arteriosus, Eisenmenger complex, and differential cyanosis: A case report. Issue 24 (June 2017) - Lin, Ting-Wei; Tseng, Chih-Wei; Huang, Chi-Yao; Wang, Kuo-Yang; Liang, Kae-Woei
Abstract: Rationale: Few studies had reported syndromes that include patent ductus arteriosus (PDA) with Eisenmenger syndrome and congenital deafness clustered in male siblings without facial, skeletal, or mental abnormalities. Patient concerns: Two brothers, who were deaf and had PDA with Eisenmenger complex, were first seen at our Cardiology clinic at the ages of 25 and 41, respectively. They presented with progressive dyspnea on exertion. Upon physical examination, both brothers had clubbing and/or cyanotic toes, normal fingers, and without facial, skeletal, ophthalmological, or mental abnormalities. Diagnoses and interventions: Echocardiography and multidetector computed tomography revealed large PDAs in both brothers. Cardiac catheterization showed bidirectional shunting via the PDA. Outcomes and lessons: Familial clustering of Eisenmenger PDA and congenital deafness is rare. Further studies are warranted to define possible genetic links.